(untitled) (The Peerian Journal, 2024)
Fever is a common symptom of many infections, e.g., in the ongoing COVID-19 pandemic, keeping monitoring devices such as thermometers in constant demand. Recent technological advancements have made infrared (IR) thermometers the choice for contactless screening of multiple individuals. Yet, even so, the measurement accuracy of such thermometers is affected by many factors including the distance from the volunteers’ forehead, To realize the human body temperature fast and non-contact measurement, an infrared thermometer is designed. The infrared human body temperature sensor is mainly used to convert the human body’s infrared into a voltage signal, an operational amplifier to amplify the signal, a filter circuit to filter the signal, the analog signal into a digital signal by the A/D conversion circuit, data processing by the MCU, LCD display reporting body temperature, we also found ways to program compensation methods for the final assembled digital IR thermometer to provide more accurate readings and measurements